Exploration of Daphnia behavioral effect profiles induced by a broad range of toxicants with different modes of action. (22nd June 2015) - Chevalier, Julie; Harscoët, Elodie; Keller, Merlin; Pandard, Pascal; Cachot, Jérôme; Grote, Matthias
Abstract: Behavior is increasingly reported as a sensitive and early indicator of toxicant stress in aquatic organisms. However, the systematic understanding of behavioral effects and comparisons between effect profiles is hampered because the available studies are limited to few chemicals and differ in the exposure conditions and effect parameters examined. The aims of the present study were 1) to explore behavioral responses of Daphnia magna exposed to different toxicants, 2) to compare behavioral effect profiles with regard to chemical modes of action, and 3) to determine the sensitivity and response time of behavioral parameters in a new multi‐cell exposure system named Multi‐DaphTrack compared with currently utilized tests. Twelve compounds covering different modes of toxic action were selected to sample a wide range of potential effect profiles. Acute standard immobilization tests and 48 h of behavioral tracking were performed in the customized Multi‐DaphTrack system and a single‐cell commercialized biological early warning system. Contrasting behavioral profiles were observed for average speed (i.e., intensity, time of effect onset, effect duration), but no distinct behavioral profiles could be drawn from the chemical mode of action. Most compounds tested in the Multi‐DaphTrack system induced an early and significant average speed increase at concentrations near or below the 10% effective concentration (48 h) of the acute immobilization test, demonstrating that the Multi‐DaphTrack system is fast and sensitive. To conclude, behavior endpoints could be used as an alternative or complement to the current acute standard test or chemical analysis for the predictive evaluation of ecotoxic effects of effluents or water bodies. Environ Toxicol Chem 2015;34:1760–1769. © 2015 SETAC